Biomarkers of diabetes risk in the National Diet and Nutrition Survey rolling programme (2008-2011) - AlMoosawi, Suzana; Cole, D.; Nicholson, S.; Bayes, I.; Teucher, Birgit; Bates, B.; Mindell, J.; Tipping, S.; Deverill, C.; Stephen, A. M. (Journal of epidemiology and community health, 2014)
This study describes the distribution of glycosylated haemoglobin (HbA1c) and glucose concentrations in the combined year 1 (2008-2009), year 2 (2009-2010) and year 3 (2010-2011) of the National Diet and Nutrition Survey (NDNS) rolling programme. The NDNS rolling programme is a nationally representative survey of food consumption, nutrient intakes and nutritional status of people aged 1.5 years and over living in England, Wales, Scotland and Northern Ireland. The study population comprised survey members who completed three or four days of dietary recording and who provided a blood sample. After excluding survey members with self-reported diabetes (n=25), there were 1016 results for HbA1c and 942 for glucose (not the same individuals in each case). Around 5.4% of men and 1.7% of women aged 19-64 years, and 5.1% of men and 5.9% of women aged ≥65 years had impaired fasting glucose (glucose concentrations 6.1-6.9 mmol/L). Over 20% of men aged ≥65 years had fasting glucose concentrations above the clinical cut-off for diabetes (≥7 mmol/L) compared to 2.1% of women of similar age (p=0.007). Similarly, 16.4% of men had HbA1c concentrations ≥6.5%, compared to 1.5% of women (p=0.003). Children and teenagers had fasting glucose and HbA1c values largely within the normal range. To conclude, this is the first study to provide data on the distribution of HbA1c and glucose concentrations in a nationally representative sample of the British population. The high prevalence of men aged ≥65 years with HbA1c and glucose concentrations above the clinical cut-off of diabetes warrants further attention.
Published online first 19 September 2013
Gesehen am 28.09.2021